Visualization of Left Ventricular Endocardium Activation Time during Cardiac Conduction System Pacing - Perepeka, Eugene O. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. Right ventricular myocardial pacing leads to asynchronous contraction of the left ventricle (LV) and can impair its contractility over time. Stimulation of the conduction system of the heart ensures physiological activation of the ventricles. The aim. To visualize the pattern of propagation of the electrical front on the activation map of the LV endocardium during conduction system pacing and during right ventricular myocardial pacing. Materials and methods. In two patients with the conduction system pacing, who were operated at the National Amosov Institute of Cardiovascular Surgery, invasive LV activation mapping was performed on various options of cardiac pacing using the EnSite Precision TM navigation system. One patient with complete atrioventricular block had nonselective His bundle pacing. The second patient had dilated cardiomyopathy and indications for cardiac resynchronization therapy and ablation of the atrioventricular junction due to chronic tachyform of atrial fibrillation. After an unsuccessful attempt to place LV lead in coronary sinus, a lead for left bundle branch pacing was implanted. Different activation maps of the LV endocardium were built in two patients with two types of cardiac pacing: right ventricular myocardial pacing and cardiac conduction system pacing. Results. The total LV endocardial activation time was significantly different in the two studied patients with different pacing options. In a patient with non-selective stimulation of His bundle, the total LV endocardial activation time was 43 ms (QRS width 126 ms, the interval from the stimulus to the peak of the R wave in lead V6 78 ms). After switching to right ventricular myocardial pacing with a decrease in the pacing amplitude, the total LV endocardial activation time prolonged to 90 ms (QRS width 165 ms, the interval from the stimulus to the peak of the R wave in lead V6 117 ms). In a patient with left bundle branch pacing, total LV endocardial activation time was 51 ms (QRS width 160 ms, the interval from the stimulus to the peak of the R wave in lead V6 66 ms). With switching exclusively to right ventricular pacing the total LV endocardial activation time prolonged to 93 ms (stimulated QRS width 180 ms). At the same time, the activation pattern of the LV endocardium was significantly different, since the right ventricular lead was located closer to the apex. Conclusions. Conduction system pacing provides rapid physiological LV activation and potentially avoids the negative consequences of asynchronous slow ventricular activation during right ventricular pacing.